Use of the Phantom Electrode strategy to improve bass frequency perception for music listening in cochlear implant users. (September 2015) - Munjal, Tina; Roy, Alexis T.; Carver, Courtney; Jiradejvong, Patpong; Limb, Charles J.
Abstract : Objectives: The Phantom Electrode strategy makes use of partial bipolar stimulation on the two most apical electrodes in an effort to extend the frequency range available to cochlear implant (CI) users. This study aimed to quantify the effect of the Phantom Electrode strategy on bass frequency perception in music listening in CI users. Methods: Eleven adult Advanced Bionics users with the Fidelity 120 processing strategy and 16 adult normal hearing (NH) individuals participated in the study. All subjects completed the CI-multiple stimulus with hidden reference and anchor (MUSHRA), a test of an individual's ability to make discriminations in sound quality following the removal of bass frequency information. NH participants completed the CI-MUSHRA once, whereas CI users completed the task twice – once with their baseline clinical program and once with the Phantom Electrode strategy, in random order. CI users' performance was assessed in comparison with NH performance. Results: The Phantom Electrode strategy improved CI users performance on the CI-MUSHRA compared with Fidelity 120. Discussion: Creation of a Phantom Electrode percept through partial bipolar stimulation of the two most apical electrodes appears to improve CI users' perception of bass frequency information in music, contributing to greater accuracy in the ability to detect alterations in musical sound quality. Conclusion: The Phantom Electrode processing strategy may enhance the experience of listening to music and thus acoustic stimuli more broadly by improving perception of bass frequencies, through direction of current towards the apical portion of the cochlea beyond the termination of the electrode.